위치센서가 없는 영구자석형 동기전동기의 파라미터 측정 - 정영석(Young-Seok Jung) (동력시스템공학회지, 2024)
영구자석형 동기전동기의 고효율 운전을 위해서는 전동기 파라미터에 대한 정보가 필수적이다. 복잡한 추정 알고리즘이나 별도의 평가장치 없이 개발 제어보드를 이용할 경우, 전동기 파리미터 측정을 위해 임의의 전압 또는 전류를 권선에 흘려 측정할 수 있으나, 기존에는 회전자의 위치센서가 있는경우에 대한 연구만 보고되었다. 본 논문에서 회전자 위치 센서가 없는 경우의 전동기 파라미터 측정을 위한 방안을 제시한다. 측정한 파라미터를 이용하여 전류제어기 및 속도제어기를 설계하여 원하는제어성능을 만족함을 보인다. 제시한 방법의 유용성을 확인하기 위해 실험으로 검증한다. For high-efficiency operation of permanent magnet synchronous motors, information about motor parameters is essential. When using a development control board without a complex algorithm or separate evaluation device, arbitrary voltage or current can be measured by flowing through the windings to measure motor parameters. However, existing studies have only been reported on cases with a rotor position sensor. In this paper, we present a method for measuring motor parameters when there is no rotor position sensor. It is shown that the desired control performance is satisfied by designing a current controller and a speed controller using the measured parameters. To confirm the usefulness of the proposed method, it is verified through experiments. KCI Citation Count: 0